Laszlo zechmeister : his life and pioneering work in chromatography - Wirth, Michaela (SpringerBriefs in Molecular Science, 2013)
Lázlo Zechmeister was one of the pioneers in chromatology. He recognized the potential of the chromatographic method and made extensive use of it for his research about natural products. In 1938 he founded the book series "Progress in the Chemistry of Organic Natural Products" which includes review articles on contemporary research by masters in their fields of expertise. This text casts light on his life and his pioneering role in chromatography and provides more detailed insight on the book series.